Design and evaluation of a high rate mode i translaminar fracture toughness test for composite laminates - Robinson,P; McCarroll,CA; Pinho,ST; Iannucci,L; Curtis,PT (2012)
The compact tension (CT) specimen has been investigated for the measurement of the high rate Mode I translaminar toughness of a carbon epoxy composite laminate with a layup of [(90°/0°)890°] s. Finite element analyses using LS-DYNA showed that when loaded at high rates (up to 12 m/s) the CT specimen achieved virtually pure Mode I fracture. In additional analyses a data-reduction strategy was developed in which strain (measured at a specific position on the specimen) and crack length measured during a test could be used to determine the toughness in high rate tests. In an experimental programme the average propagation toughness exhibited a small overall decrease with increasing test speed but, in view of the considerable scatter, further testing will be required to confirm the significance of this trend. Examination of the fracture surfaces using a scanning electron microscope indicated that the fracture characteristics are essentially unchanged with increasing test speed.